Competitiveness and Economic Security - Priority Problems of the Region’s Metallurgical Comples and Its Leaders in the Conditions Of Instability - Kozitsyn, Andrey Anatolyevich; Dudinskaya, Margarita Vitalyevna (Economy of Regions, 2015)
The subject-matter of the research is the study of the regional metallurgical complex and its leaders, which account for 55 % of industrial output and more than 57 % of exports of the Sverdlovsk region, in the current terms of economic instability. Supporting the business priorities of improving the competitiveness and economic security of the enterprise is based on the example of "UMMC- Holding" - the leader of ferrous metallurgy in the Middle Urals, an active participant in the global and Russian copper market. The modern economic, mathematical, and general scientific methods (comparison study, the ratio of total and private, and others) are applied as the research methods. To obtain the study results, the main areas of the holding impacted by the sanctions are analyzed: modernization of production and spare parts provisions of the current imported equipment, correction of the supply chain, searching for new business partners, transformation of the structure and direction of cargo traffic, solving transportation problems, stocks system management and minimization of economic, social and environmental costs. The urgency of solving the problem of company competitiveness and economic security increasing together with its sectoral and regional features in the present conditions is proved as the key conclusion. The high competitiveness of the holding is considered to be one of the factors of its economic security. The main goal of the economic security of the company is its sustainable and maximally effective functioning at the present time and high potential for successful development in the future. The indicators and criteria for the economic security evaluation are studied in detail. The analysis conducted has shown that, in general, the holding has high indicators characterizing its economic security on the basis of high competitiveness. As a negative sign, a lack of the investment growth needed to solve urgent problems is noticed.